New species and records of Evanioidea and Stephanoidea from New Caledonia (Hymenoptera) - Ramage, Thibault; Jouault, Corentin (European Journal of Taxonomy, 2020)
Three new species of aulacid wasps, Aulacus pascali sp. nov., Pristaulacus elveni sp. nov. and Pristaulacus villemantae sp. nov., and a new species of gasteruptiid wasp, Gasteruption jenningsi sp. nov., are described and figured. Additionally, we update identification keys to New Caledonia species of aulacids and gasteruptiids. We also provide new data on New Caledonian Evaniidae, Gasteruptiidae and Stephanidae.